Teori Belajar dan Implikasinya dalam Manajemen Pengembangan Kurikulum - M Rafieq Adi Pradana (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This study examines educational theories from experts and is accompanied by the author's opinion about learning theory and its implications for the management of school curriculum development. This research begins with the idea that one of the functions of education must be able to equip students with knowledge that can be useful in the future, and one of the keys to successful education lies in the curriculum, for this reason the curriculum must be adapted to the situation and conditions of natural resources and human resources. human power. This research is an academic field research that is oriented towards the development of knowledge, with naturalistic methods, descriptive qualitative, with a Grounded Theory strategy, the technique used is library research with written records as data sources from books, journals, etc. analyzed with Content Analysis technique. In the study of the data it was found that learning is a positive change in the behavior of students from those who do not understand to understand, from those who cannot yet become able, and from those who are not good enough to be better. Learning Types are divided into Visual, Auditory, and Kinesthetic. Students with the visual learning type tend to access information via visuals (vision), colors and images stand out in this type. Students with the type of Auditory Learning (hearing) tend to learn and access information through music, dialogue, and sound which is prominent in this type. Meanwhile, students with the kinesthetic learning type access information through movement and emotion, movement. Coordination, emotional response and physical comfort predominate here. The curriculum is a guideline in education, its components namely Objectives, Materials, Methods, Organization, and Evaluation. The curriculum development stage is the planning stage. Implementation stage, and evaluation stage. Learning theory is a principle related to learning. There are three learning theories, including faculty theory, which focuses on students' power abilities, Association theory, which focuses on student response processes to lessons or stimuli, and field theory, which focuses on mastery of understanding. Curriculum development management based on faculty theory is developed by setting educational goals that focus on honing students' abilities, then in practice providing materials and methods that give a large portion of training, in order to hone children's power, in an organized manner not prioritizing thematic, but more on in the field of children's abilities, while the evaluation does not judge much on the extent to which the material is achieved (cognitive), but rather on the extent to which students develop in improving their abilities and skills (psychomotor), but that does not mean ignoring other aspects. a curriculum based on association theory is developed by means of setting educational goals focusing on communication between teachers and students, then in practice teachers are required to be more active in providing material, questions, assignments to students (Stimulus), so students will be trained to answer or respond to teacher assignments by good. Evaluation is more inclined to the process, the extent to which students' attitudes respond to assignments not to the results of their work (affective), but that does not mean ignoring other aspects. With field theory, the curriculum is developed by setting goals that emphasize the demands of understanding concepts that are so strong, because it is believed that with the concepts mastered, other new concepts can be applied. and fundamental, while the evaluation tends to understand the material (cognitive), but that does not mean ignoring other aspects